2012
DOI: 10.1183/09031936.00124312
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of meropenem–clavulanate added to linezolid-containing regimens in the treatment of MDR-/XDR-TB

Abstract: Clinical experience on meropenem-clavulanate to treat tuberculosis (TB) is anecdotal (according to case reports on 10 patients). The aim of our case-control study was to evaluate the contribution of meropenem-clavulanate when added to linezolid-containing regimens in terms of efficacy and safety/tolerability in treating multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB cases after 3 months of second-line treatment.37 cases with MDR-/XDR-TB were prescribed meropenem-clavulanate (3 g daily dose) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 24 publications
2
116
0
5
Order By: Relevance
“…As it must be recognised, following current trends, Europe is unlikely to achieve elimination of the disease by the target date of 2050 [23,24], we urgently need new vaccines, as well as improved diagnostics [25,26] and new drugs [27][28][29]. With respect to economic considerations, the aim of the present study was to evaluate the costs associated with TB disease in order to determine whether they outweigh the investment needed to generate a new vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…As it must be recognised, following current trends, Europe is unlikely to achieve elimination of the disease by the target date of 2050 [23,24], we urgently need new vaccines, as well as improved diagnostics [25,26] and new drugs [27][28][29]. With respect to economic considerations, the aim of the present study was to evaluate the costs associated with TB disease in order to determine whether they outweigh the investment needed to generate a new vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study 62 it demonstrated, when added to linezolid-containing OBR, to improve sputum smear and culture conversion in MDRand XDR-TB cases. Further studies are necessary to define the role of this drug within the anti-MDR-TB armamentarium.…”
Section: Re-proposed Drugsmentioning
confidence: 98%
“…Imipenem/cilastatin and meropenem, combined with clavulanic acid, seem to have a promising activity, while being well tolerated (34)(35)(36)(37). In the direct comparison meropenem performs better than imipenem (37).…”
Section: Which Drugs Might Be Upgradedmentioning
confidence: 99%